2019
DOI: 10.1017/s1092852919001287
|View full text |Cite
|
Sign up to set email alerts
|

Cariprazine efficacy in bipolar I depression with and without concurrent manic symptoms: post hoc analysis of 3 randomized, placebo-controlled studies

Abstract: Objective. Mixed presentations, defined by simultaneous occurrence of depressive and manic symptoms, are difficult to treat. Antidepressants, although commonly used, have weak evidence of efficacy and may increase risk of mood destabilization. The aim of this pooled post hoc analysis was to evaluate the efficacy of cariprazine in the treatment of bipolar depression with or without concurrent manic symptoms. Methods. Patients from 3 randomized, double-blind, placebo-controlled studies who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(14 citation statements)
references
References 36 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…In a post hoc analysis of all three of these studies pooled together to investigate cariprazine’s efficacy in depression with symptoms of mania, it was determined that 58.4% of the 1483 patients randomized to treatment had concurrent manic symptoms (YMRS score ⩾4 but <10 (1 study) or 12 (2 studies) (Table 4). 31 Both patients with and without manic symptoms showed significant improvement in MADRS score from baseline compared with placebo, but for patients with manic symptoms, both 1.5 mg/day and 3.0 mg/day were significant but only 1.5 mg/day was significant for patients without manic symptoms (Table 4). 31…”
Section: Cariprazine Clinical Efficacymentioning
confidence: 94%
See 2 more Smart Citations
“…In a post hoc analysis of all three of these studies pooled together to investigate cariprazine’s efficacy in depression with symptoms of mania, it was determined that 58.4% of the 1483 patients randomized to treatment had concurrent manic symptoms (YMRS score ⩾4 but <10 (1 study) or 12 (2 studies) (Table 4). 31 Both patients with and without manic symptoms showed significant improvement in MADRS score from baseline compared with placebo, but for patients with manic symptoms, both 1.5 mg/day and 3.0 mg/day were significant but only 1.5 mg/day was significant for patients without manic symptoms (Table 4). 31…”
Section: Cariprazine Clinical Efficacymentioning
confidence: 94%
“…31 Both patients with and without manic symptoms showed significant improvement in MADRS score from baseline compared with placebo, but for patients with manic symptoms, both 1.5 mg/day and 3.0 mg/day were significant but only 1.5 mg/day was significant for patients without manic symptoms (Table 4). 31…”
Section: Efficacy In Bp Depression With or Without Concomitant Symptoms Of Maniamentioning
confidence: 94%
See 1 more Smart Citation
“…Post-hoc analyses of a number of positive randomized, placebocontrolled trials of second-generation antipsychotics in bipolar depression have explored response of depression with hypo/manic symptoms vs pure depression (ie, bipolar depression with no hypo/manic symptoms). These studies found that olanzapine (with and without fluoxetine), 50,51 lurasidone, 52 and cariprazine 53 were as effective in mixed depression as in pure depression. A similar analysis showed that lurasidone reduced mixed features in children with bipolar depression.…”
Section: Post-hoc Analyses Of Randomized Placebo-controlled Trials Of Second-generation Antipsychotics In Bipolar Depressionmentioning
confidence: 99%
“…Furthermore, incidence of suicidality was low in cariprazine group ( 73 ). Finally, a post-hoc analysis of three randomized, placebo-controlled studies showed that cariprazine is effective in treating bipolar I depression with mixed features in the doses of 1.5 and 3.0 mg per day ( 74 ).…”
Section: Cariprazine Efficacy Across the Wide Range Of Symptoms Of Bipolar Disordermentioning
confidence: 99%